Dynamics of Candidatus Liberibacter asiaticus Movement and Sieve-Pore Plugging in Citrus Sink Cells. Issue 2 (9th December 2019) - Achor, Diann; Welker, Stacy; Ben-Mahmoud, Sulley; Wang, Chunxia; Folimonova, Svetlana Y.; Dutt, Manjul; Gowda, Siddarame; Levy, Amit
Abstract : The phloem-limited Gram-negative bacterium Candidatus Liberibacter asiaticus interacts with the phloem membranes of citrus species and can change its form to move through the phloem pores. Abstract: Citrus greening or Huanglongbing (HLB) is caused by the phloem-limited intracellular Gram-negative bacterium Candidatus Liberibacter asiaticus (CLas). HLB-infected citrus phloem cells undergo structural modifications that include cell wall thickening, callose and phloem protein induction, and cellular plugging. However, very little is known about the intracellular mechanisms that take place during CLas cell-to-cell movement. Here, we show that CLas movement through phloem pores of sweet orange ( Citrus sinensis ) and grapefruit ( Citrus paradisi ) is carried out by the elongated form of the bacteria. The round form of CLas is too large to move, but can change its morphology to enable its movement. CLas cells adhere to the plasma membrane of the phloem cells specifically adjacent to the sieve pores. Remarkably, CLas was present in both mature sieve element cells and nucleated nonsieve element cells. The sieve plate plugging structures of host plants were shown to have different composition in different citrus tissues. Callose deposition was the main plugging mechanism in the HLB-infected flush, where it reduced the open space of the pores. In the roots, pores were surrounded by dark extracellular material, with very little accumulation of callose. The expression of CALLOSE SYNTHASE7 and PHLOEM PROTEIN2 genes was upregulated in the shoots, but downregulated in root tissues. In seed coats, no phloem occlusion was observed, and CLas accumulated to high levels. Our results provide insight into the cellular mechanisms of Gram-negative bacterial cell-to-cell movement in plant phloem.